2007
DOI: 10.1590/s1517-86922007000200007
|View full text |Cite
|
Sign up to set email alerts
|

Teste de caminhada de seis minutos na doença pulmonar obstrutiva crônica com diferentes graus de obstrução

Abstract: INTRODUÇÃO: Alguns testes funcionais são utilizados complementando a avaliação dinâmica na doença pulmonar obstrutiva crônica (DPOC), como o teste de caminhada de seis minutos (TC6). OBJETIVOS: Verificar quanto o grau de obstrução compromete a tolerância ao esforço avaliado pelo TC6 e comparar a distância percorrida e prevista através da equação de Enright e Sherrill (1998) para indivíduos saudáveis e com DPOC apresentando grau de obstrução leve, moderado e grave, além de comparar a distância percorrida entre … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 24 publications
1
3
0
7
Order By: Relevance
“…We observed that as we find in the literature (6,7,8,9,10), this study results shows that 6MWT could be increasingly used as coadjutant or alternative to evaluate cardiac patients who are submitted to cardiac rehabilitation.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…We observed that as we find in the literature (6,7,8,9,10), this study results shows that 6MWT could be increasingly used as coadjutant or alternative to evaluate cardiac patients who are submitted to cardiac rehabilitation.…”
Section: Discussionsupporting
confidence: 80%
“…The assessment of physical capacity is performed with functional physical tests, as the six-minute walk test (6MWT), which is applied with the purpose to complement the dynamic evaluation of CD subjects, analyze the effectiveness of treatment and to establish prognosis (5,6,7,8,9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esta prueba, inicialmente, se realizaba apenas con individuos saludables, pero actualmente ha sido usada en portadores de patologías y también para evaluar la aptitud 16 física de adultos mayores en relación al consumo de O . 2 Por tratarse de un método simple y fácil, es bastante utilizado en análisis para evaluar capacidad en ejercicios, tiene además un bajo costo financiero y presenta validez 5,16 para experimentar el sistema cardiorrespiratorio .…”
Section: Instrumentos Utilizadosunclassified
“…2 Por tratarse de un método simple y fácil, es bastante utilizado en análisis para evaluar capacidad en ejercicios, tiene además un bajo costo financiero y presenta validez 5,16 para experimentar el sistema cardiorrespiratorio .…”
Section: Instrumentos Utilizadosunclassified